Bilateral Investment Treaties in the Digital Era: Implications for Technology and Media Regulation - Mira Nila Kusuma Dewi; Nurul Miqat; Susi Susilawati; Ashar Ridwan; Abd. Basir (Universitas Negeri Semarang, 2025)
The rapid expansion of digital technologies has transformed the global investment landscape, prompting states to revisit the structure and objectives of Bilateral Investment Treaties (BITs). Initially designed to protect tangible investments through guarantees such as fair and equitable treatment (FET), non-discrimination, and protection against expropriation, BITs now confront a new set of regulatory challenges associated with cross-border data flows, platform governance, and digital sovereignty. The rise of technology and media platforms-characterized by their intangible, mobile, and data-driven nature-raises fundamental questions regarding the definition of “investment,” the scope of investor rights, and the extent of state regulatory space. This article examines the evolution of BITs in the digital era using a normative juridical method, focusing on how international investment law interacts with technology and media regulation. Through analysis of key jurisprudence, particularly Yahoo! Inc. v. LICRA and UEJF and the Schrems I & II decisions of the Court of Justice of the European Union (CJEU), the study demonstrates that the digital ecosystem demands more adaptive treaty frameworks capable of balancing investor protection with legitimate regulatory objectives such as privacy, cybersecurity, and content governance. The article also evaluates Indonesia’s regulatory landscape, including the Information and Electronic Transactions Law (UU ITE) and the Personal Data Protection Law (UU PDP), to illustrate national perspectives on digital governance within the broader BIT reform movement. Ultimately, this research argues that BITs must incorporate explicit digital-era provisions-such as data governance carve-outs, cybersecurity exceptions, and right-to-regulate clauses-to safeguard state sovereignty and public interests while maintaining a predictable investment environment.